Data‐driven learning and planning for environmental sampling - Ma, Kai‐Chieh; Liu, Lantao; Heidarsson, Hordur K.; Sukhatme, Gaurav S. (Journal of field robotics, 2018)
Robots such as autonomous underwater vehicles (AUVs) and autonomous surface vehicles (ASVs) have been used for sensing and monitoring aquatic environments such as oceans and lakes. Environmental sampling is a challenging task because the environmental attributes to be observed can vary both spatially and temporally, and the target environment is usually a large and continuous domain whereas the sampling data are typically sparse and limited. The challenges require that the sampling method must be informative and efficient enough to catch up with the environmental dynamics. In this paper, we present a planning and learning method that enables a sampling robot to perform persistent monitoring tasks by learning and refining a dynamic “data map” that models a spatiotemporal environment attribute such as ocean salinity content. Our environmental sampling framework consists of two components: To maximize the information collected, we propose an informative planning component that efficiently generates sampling waypoints that contain the maximal information; to alleviate the computational bottleneck caused by large‐scale data accumulated, we develop a component based on a sparse Gaussian process whose hyperparameters are learned online by taking advantage of only a subset of data that provides the greatest contribution. We validate our method with both simulations running on real ocean data and field trials with an ASV in a lake environment. Our experiments show that the proposed framework is both accurate in learning the environmental data map and efficient in catching up with the dynamic environmental changes.